2014
DOI: 10.1179/1743289814y.0000000108
|View full text |Cite
|
Sign up to set email alerts
|

Tensile behaviour of carbon nanotube/polypropylene composite material

Abstract: The tensile behaviour of the polypropylene (PP) material reinforced by multiwalled carbon nanotubes (MWCNTs) was characterised by mechanical testing. Two different MWCNT weight ratios, namely 2 and 5%, were considered. The strains were measured using strain gauges and a digital image correlation system. The results from mechanical tests were evaluated using scanning electron microscopy (SEM). An increase in the average Young's modulus of 20?29 and 25?19% and in average maximum stress of 26?13 and 33?31% was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In a previous study [10] the tensile behavior of the Plasticyl TM PP2001 material has been characterized experimentally. This is a PP material reinforced by multi-walled CNTs (MWCNTs).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study [10] the tensile behavior of the Plasticyl TM PP2001 material has been characterized experimentally. This is a PP material reinforced by multi-walled CNTs (MWCNTs).…”
Section: Methodsmentioning
confidence: 99%
“…For demonstration reasons, the model was developed on the basis of the CNT/PP material. The values of design parameters were determined from scanning electron microscopy (SEM) images presented in [10]. This was also necessary because one of the objectives of the present work is to use the RUC as a module of a two-scale model to evaluate the Young's modulus of the CNT/PP material.…”
Section: Design Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a multifunctional material could be a load-bearing material with excellent thermal and electrical properties providing the structure enhanced resistance to lighting strike and great shielding effectiveness against electromagnetic interference [1]. Nanocomposites (polymers filled by carbon nanotubes (CNTs)) could achieve all these functions due to their excellent mechanical [2][3][4][5][6], thermal [7][8][9] and electrical [10][11][12][13][14][15][16] assigned by the CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Early experimental studies [6,[7][8][9][10][11][12][13] have revealed that the properties of CNT/polymer nanocomposites are governed by several material parameters and processing factors and in some cases might be contradictory. Therefore, the development of multifunctional nanocomposites must undergo a proper design and optimization phase which can be performed either by repeated manufacturing trials and physical testing or by virtual testing.…”
Section: Introductionmentioning
confidence: 99%